Influence of initial treatment delay on overall survival and event-free survival in childhood acute lymphoblastic leukemia - Irenne Purnama; Pudjo Hagung Widjajanto; Wahyu Damayanti (Indonesian Pediatric Society, 2021)
Background Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy. Initial treatment delay is a modifiable prognostic factor that significantly affects overall survival (OS) and event-free survival (EFS) of childhood ALL in high-income countries. Nevertheless, the effect of delayed initial treatment in low-middle income countries had not been determined. Objective To analyze relationships between initial treatment delay with overall survival and event-free survival in children with ALL. Methods A retrospective study was conducted in children aged < 18 years newly diagnosed with ALL L1 and L2 from January 2013 until December 2018 at Dr. Sardjito Hospital, Yogyakarta. Initial treatment delay was defined as a time interval of more than 3 days between diagnosis and treatment. The outcomes of the study were OS and EFS. Negative events were defined as remission failure, relapse, dropping out, and death. Overall survival (OS) and event free survival (EFS) were analyzed by Kaplan-Meier and log-rank tests. Results Of 341 subjects, 188 (55.5%) underwent delayed initial treatment. There were no significant relationships between initial treatment delay and OS (HR 0.845; 95%CI 0.548 to 1.302; P=0.445) or EFS (HR=0.937; 95%CI 0.689 to 1.275; P=0.971). Multivariate analysis revealed that age was an independent prognostic factor for both OS (P<0.001) and EFS (P<0.001). Conclusion Initial treatment delay is not associated with OS or EFS. Age is an independent predictor for both OS and EFS.